Multicentre analysis of the learning curve for laparoscopic liver resection of the posterosuperior segments. Issue 11 (23rd August 2019) - Berardi, G.; Aghayan, D.; Fretland, Å. A.; Elberm, H.; Cipriani, F.; Spagnoli, A.; Montalti, R.; Ceelen, W. P.; Aldrighetti, L.; Abu Hilal, M.; Edwin, B.; Troisi, R. I.
Abstract : Background: Laparoscopic liver resection demands expertise and a long learning curve. Resection of the posterosuperior segments is challenging, and there are no data on the learning curve. The aim of this study was to evaluate the learning curve for laparoscopic resection of the posterosuperior segments. Methods: A cumulative sum (CUSUM) analysis of the difficulty score for resection was undertaken using patient data from four specialized centres. Risk‐adjusted CUSUM analysis of duration of operation, blood loss and conversions was performed, adjusting for the difficulty score of the procedures. A receiver operating characteristic (ROC) curve was used to identify the completion of the learning curve. Results: According to the CUSUM analysis of 464 patients, the learning curve showed an initial decrease in the difficulty score followed by an increase and, finally, stabilization. More patients with cirrhosis or previous surgery were operated in the latest phase of the learning curve. A smaller number of wedge resections and a larger number of anatomical resections were performed progressively. Dissection using a Cavitron ultrasonic surgical aspirator and the Pringle manoeuvre were used more frequently with time. Risk‐adjusted CUSUM analysis showed a progressive decrease in operating time. Blood loss initially increased slightly, then stabilized and finally decreased over time. A similar trend was found for conversions. The learning curve was estimated to be 40 procedures for wedge and 65 for anatomical resections. Conclusion: The learning curve for laparoscopic liver resection of the posterosuperior segments consists of a stepwise process, during which accurate patient selection is key. Abstract : The learning curve for laparoscopic liver resection of lesions located in the posterosuperior segments consists of a stepwise process in which patient selection plays the most important role. Stepwise approach sensible Abstract: Antecedentes: La resección hepática laparoscópica exige experiencia y una larga curva de aprendizaje. La resección de los segmentos posterosuperiores (PS) es un reto, y no hay datos acerca de la curva de aprendizaje ( learning curve, LC). El objetivo de este estudio fue evaluar la LC de la resección laparoscópica de los segmentos PS. Métodos: Se realizó un análisis CUSUM de la puntuación de dificultad ( difficulty score, DS) de la resección en pacientes de 4 centros especializados. La técnica CUSUM se ajustó al riesgo ( risk‐adjust ed CUSUM, RA‐CUSUM) para el tiempo operatorio, la pérdida de sangre y las conversiones a cirugía abierta ajustando según la DS de los procedimientos. Se utilizó una curva ROC para identificar el momento en el que se consideró que la LC había sido completada. Resultados: De acuerdo con el análisis CUSUM de los 464 pacientes incluidos, se observó una DS baja al inicio, que posteriormente se fue incrementando hasta llegar a una estabilización. En la última fase de la LC se operaron más pacientes con cirrosis o cirugía previa. De forma progresiva se fueron reduciendo el número de resecciones hepáticas en cuña y aumentando el de resecciones anatómicas. A lo largo del tiempo se introdujo el CUSA y la maniobra de Pringle con mayor frecuencia. El RA‐CUSUM mostró una reducción progresiva del tiempo operatorio. La pérdida de sangre inicialmente aumentó ligeramente, luego se estabilizó y finalmente disminuyó con el tiempo. Una tendencia similar se observó para las conversiones. La LC se estimó en 40 casos para las resecciones en cuña y en 65 casos para las resecciones anatómicas. Conclusión: La LC de la resección hepática laparoscópica de los segmentos PS es un proceso paso a paso durante el cual la selección del paciente es clave.